HADIS-HADIS RAJA’ DAN PENERAPANNYA DALAM MENGATASI STRES SEORANG IBU AKIBAT SUDDEN DEATH PADA ANAKNYA DI LINGKUNGAN GLADAK PAKEM, KECAMATAN SUMBERSARI, KABUPATEN JEMBER - Nur Kholis bin Kurdian (Al-Majaalis : Jurnal Dirasat Islamiyah, 2021)
This study aims to determine the effectiveness of the application of the hadiths of hope in dealing with the stress of a mother due to sudden death in her child in Gladak Pakem, Sumbersari District, Jember Regency. This research is an action research conducted in two cycles, namely cycle I and cycle II. Each cycle consists of four stages, namely planning, acting, observing, and reflecting. The data collection techniques in this study were observation and interviews. The action taken was to provide assistance to the mother by providing advice extracted from the hadiths of hope. The delivery of advice is done verbally, continuously, and adapted to the situation and condition of the mother. The result of the action in the first cycle was a 33,3% reduction in the mother's stress level, while the rest was still 66,7%. Based on these results, it is necessary to carry out a follow-up process by taking action in cycle II. Furthermore, the results in cycle II showed a significant 90% reduction in stress levels which was indicated by an increase in the percentage of the relaxation level, while the rest was only 10%. Based on the indicators, it can be stated that the action in cycle II has been successful, so it can be concluded that the application of the hadiths of hope can overcome a mother's stress due to sudden death in her child in Gladak Pakem, Sumbersari District, Jember Regency.